Quiste glóbulo-maxilar. Caso clínico - Peláez Estrada, Edgar (Revista Estomatología, 1991)
The globulomaxilar cyst is found in the incisive suture between the lateral incisor and the maxilary canine. It many cause divarication of the adjancent roots, eventhough there is no pain and the vitality of the neighbouring teeth is unaffected. Radiographic examination shows an inverted pear image that may extend into the interdental bone and reach the alveolar crest. The treatment of choice is enucleation of the cyst. A case of globulomaxilar cyst in a 20 years old woman will be reported describing the surgical technique and endodontric therapy required in this case.